Improving Rural Household Income Through Microcredit Scheme Focused On Women in Northern Cross River: A Statistical Analysis - Thomas A. Omang; Mary U. Ojong-Ejoh; Emmanuella Dike; Bassey E. Butum; Adeolu Ayodele (SAINSMAT: Journal of Applied Sciences, Mathematics, and Its Education, 2021)
The study objective is to analyze the effect microcredit scheme on household income in Northern Cross River State. The convenient sampling technique was used in collecting data from three Local Government Area that make up Northern Cross River State. The Survey Monkey Sample Determinant Technique was used to arrive at a sample size of 1515, selected using a stratified and convenience sampling technique from Northern Cross River State, Nigeria. A self-developed semi-structured questionnaire was used as the instrument of data collection. Data collected was analyzed using descriptive statistics and Linear Regression. Out of the 1515 instrument distributed, 1306 was returned and used for analysis. The result revealed that all the participants were beneficiaries of Microcredit Scheme. 95.02 per cent reported that since benefitting from Microcredit scheme, their businesses have improved, and 96.78 per cent reporting that their family's living condition has improved since benefitting from microcredit scheme. The results from the descriptive analysis were subjected to parametric statistics using simple linear regression. The results review that woman involving in microcredit scheme has significantly improved household income in the Northern Cross River. This is because the result indicated an R-value of .245a. The regression ANOVA revealed that the F (1, 1307) = 83.345; p < .05, is significant. Based on this result, the study recommends a need for various enlightenment programmes to educate rural people on the benefit of obtaining microcredit for businesses and economic activities that will help move them out of poverty.